2003
DOI: 10.1385/ijgc:34:2-3:129
|View full text |Cite
|
Sign up to set email alerts
|

Local Recurrence of Rectal Cancer After Total Mesorectal Excision Without Preoperative Radiotherapy

Abstract: A low local recurrence rate can be achieved after total mesorectal excision (TME) without preoperative radiotherapy. Our results suggest using preoperative radiotherapy only for those patients who are at a higher risk for local recurrence. Staging techniques for selection of these patients are at this moments till inappropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 16 publications
0
12
0
3
Order By: Relevance
“…4 After the CT scan, the CT value was measured and analyzed based on images created using energy from 40 to 140 keV difficult to distinguish a lesion in the intestinal tract when the tumor is in the shape of a polyp when intestinal cleansing has not been performed adequately so that traces of feces remain. The optimal way to control rectal cancer requires a detailed preoperative plan along with evaluation of the grade of tumor and depth of invasion [19]. Accuracy is reported to be around 64-100 % when CT is used to determine the stage of colorectal cancer and rectal cancer, which means that the accuracy varies according to the person who reports the study results [20].…”
Section: Discussionmentioning
confidence: 99%
“…4 After the CT scan, the CT value was measured and analyzed based on images created using energy from 40 to 140 keV difficult to distinguish a lesion in the intestinal tract when the tumor is in the shape of a polyp when intestinal cleansing has not been performed adequately so that traces of feces remain. The optimal way to control rectal cancer requires a detailed preoperative plan along with evaluation of the grade of tumor and depth of invasion [19]. Accuracy is reported to be around 64-100 % when CT is used to determine the stage of colorectal cancer and rectal cancer, which means that the accuracy varies according to the person who reports the study results [20].…”
Section: Discussionmentioning
confidence: 99%
“…Avant l'avènement de l'exérèse totale du mésorectum (ETM) décrite dans les travaux de Heald et Ryall, la plupart des récidives étaient anastomotiques, centropelviennes et antérieures [1]. Actuellement, l'impact des traitements combinés (chirurgie radicale après radiochimiothérapie pour adénocarcinome rectal localement avancé) a certes réduit l'incidence des RLCR à moins de 8 %, mais en a également modifié la distribution [2] : la composante extraluminale devient plus fréquente notamment par un envahissement présacré ou des faces latérales du pelvis [3]. Une RLCR intraluminale débutante ne concerne que 15 à 25 % des malades.…”
Section: Introductionunclassified
“…Previous studies have found high rates of tumour in the circumferential resection margins; 22-27% in recent studies 68. Therefore, the optimal management of rectal cancer requires detailed preoperative planning that includes the assessment of the relation of tumour to the mesorectal fascia 9. Traditionally, surgeons have assessed patients with digital rectal examination,1012 endorectal ultrasonography, and occasionally computed tomography 1315.…”
Section: Introductionmentioning
confidence: 99%